Subcutaneous progesterone administration provides a similar ongoing pregnancy rate compared with intramuscular progesterone administration in hormone replacement therapy frozen embryo transfer cycles - Fazilet K. Boynukalin, M.D., MSc; Remzi Abali, M.D; Meral Gultomruk, B.Sc; Berfu Demir, M.D., M.Sc; Zalihe Yarkiner, M.Sc., Ph.D; Guvenc Karlikaya, M.D; Mustafa Bahceci, M.D; Dominique de Ziegler, M.D (Elsevier, 2023)
Objective: To compare the ongoing pregnancy rates (OPRs) for subcutaneous progesterone (SC-P) to intramuscular progesterone (IM-P) in hormone replacement therapy used in frozen embryo transfer (FET) cycles. Design: Prospective nonrandomized cohort study. Setting: Private fertility clinic. Patient(s): The study enrolled 224 patients scheduled for hormone replacement therapy (HRT)-FET cycles with SC-P (n = 133) or IM-P (n = 91). The route of P administration was decided according to the patient's preference and accessibility to the hospital. In the first FET cycle of a freeze-all cycle using single blastocyst transfers, a woman aged ≤35 was included. Main Outcome(s): Ongoing pregnancy (OP). Result(s): The demographic, cycle, and embryologic characteristics were similar between groups. The clinical pregnancy rates (86/133[64.7%] vs. 57/91[62.6%]); miscarriage rates (21/86 [24.4%] vs. 10/57 [17.5%]), and OPR (65/133 [48.9%] vs. 47/91 [51.6%]) were comparable between the SC-P and IM-P groups. Binary logistic regression for OP as the dependent factor revealed that blastocyst morphology was found to be a significant independent prognosticator (for poor quality embryos adjusted odds ratio, 0.11; 95% confidence interval, 0.029-0.427) and progesterone route (SC-P vs. IM-P) was an insignificant prognosticator (adjusted odds ratio, 0.694; 95% confidence interval, 0.354-1.358). Conclusion(s): The OPR for SC-P administration was similar to that for IM-P in HRT-FET cycles. The effect of ET-day P levels may vary regarding the administration route. Randomized controlled trials comparing different P administration routes are needed, and large-scale prospective trials are warranted to evaluate the ET-day P levels on pregnancy outcome.